Numerical investigation of alternating-direction method for Poisson equation with weighted integral conditions - Štikonienė, Olga; Sapagovas, Mifodijus (Lietuvos matematikos rinkinys, 2010)
The present paper deals with a generalization of the alternating-direction implicit(ADI) method for a two dimensional Poisson equation in a rectangle domain with aweighted integral boundary condition in one coordinate direction. We consider the alternatingdirection method for a system of difference equations that approximates Poisson equationwith weighed integral boundary conditions with the fourth-order accuracy. Sufficient conditionsof stability for ADI method are investigated numerically. An analysis of results ofcomputational experiments is presented.
Keywords: elliptic equation; nonlocal integral conditions; finite-difference method; alternating direction method; convergence of iterative method